Investing in Neighborhoods: The Mitigating Role of Home Mortgage Loans on Intimate Partner Violence - Boggess, Lyndsay N. (Journal of interpersonal violence, 2021)
Prior research examining how macro-level factors contribute to aggregate rates of intimate partner violence (IPV) across neighborhoods has focused almost exclusively on economic disadvantage or residential instability. Fewer studies have assessed what structural factors might ameliorate rates of domestic violence, such as economic investment. Housing investment improves communities by increasing the number of homeowners, who tend to be more committed to the neighborhood and more likely to develop strong social ties with other residents. The benefits of strong socially connected communities should extend to IPV victims, as studies have shown that female IPV victims tend to be less connected with their social environment and live in less supportive communities. This study examines the influence of external economic investment through home mortgage loans on the number of IPV incidents in a neighborhood and whether an influx of investment mitigates the negative effects of structural conditions on IPV. We examine these issues using panel data on home loan investment among neighborhoods in Cleveland, Ohio, between 1995 and 2010 to predict female and male domestic assault victimization rates. We find that the number of home purchase loans in a neighborhood has no appreciable impact on the level of IPV incidents, but as the average dollar amount of investment increases, the number of IPV incidents significantly decreases. This relationship is moderated by the neighborhood level of disadvantage: in highly disadvantaged neighborhoods, even low average dollar amounts contribute to a reduction in the number of female victims of domestic assault, but the same relationship is not apparent for male victims or in low disadvantaged neighborhoods. Our findings suggest that investment is important for disrupting the relationship between neighborhood structure and IPV, and implementing place-based strategies to encourage homeownership, particularly in disadvantaged neighborhoods, will be especially impactful.